The Discriminative Ability of the Azeri Version of the Strengths and Difficulties Questionnaire in Outpatient Practice - Salayev, Kamran (Community Ment Health J, 2014)
In this study we examined the validity of the Azeri version of the Strengths and Difficulties Questionnaire (SDQ). The SDQ was administered to the parents of two samples of 4–16-year-old children: the case group was drawn from children presenting to the psychiatric outpatient service (n = 347) and the comparison group from the pediatric outpatient service (n = 267). The total difficulties score and the scores for each subscale were compared between two groups. The proportion of children with the total difficulties score in the abnormal range was higher in the case group than in the comparison group (74 and 34 %, p <0.001). The mean difficulties score difference between two groups was significant (mean difference = 6.3, p <0.001). The Receiver Operating Characteristics analysis showed good discriminative ability for the total difficulties score and difficulties subscales (p <0.001). SDQ distinguished well between groups.